Creative ideation - Parkinson, Lee (Henry Stewart Talks, 2009)
Setting the scene, Welcome to the world of the 'new consumer'- A definition of experiential marketing, Creating an experience, In terms of marketing, what is 'experience'?, Creative ideation, Beyond the 'creative'